Compartment-specific transcription in Bacillus subtilis: identification of the promoter for gdh. - Rather, P N (1988)
Glucose dehydrogenase beings to accumulate in the forespore between 2 and 3 h after the onset of endospore formation in Bacillus subtilis. The promoter for the structural gene for glucose dehydrogenase (gdh) was shown to be located 800 base pairs upstream from the coding sequence by examining the effects of integrating plasmids into the gdh region of the chromosome. The location of the gdh promoter was confirmed by primer extension analysis and by the identification of two single-base substitutions in the gdh promoter that prevented its function. The results of cell fractionation experiments with a strain that contained a transcriptional fusion of the gdh promoter and lacZ indicated that the forespore-specific accumulation of glucose dehydrogenase during sporulation is probably due to forespore-specific transcription of gdh.